ANALISIS MUATAN NILAI KARAKTER DISIPLIN PADA FILM ANIME MIMI O SUMASEBA - Nabilah, Karla Zulfa; Hidayat, Muhamad Taufik (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
Discipline is a character trait that must be instilled from an early age, as it can help a person achieve their goals. This study aimed to analyze and describe the character values of discipline in the anime film "Mimi o Sumaseba". The method used in the study was content analysis with a descriptive design. The data were obtained from observing and recording the dialogues and scenes in "Mimi o Sumaseba", which were then collected through documentation. Data analysis utilized data reduction, data presentation, and conclusion. The validity of the data was assessed through the extension of observations and increased persistence. The results of this study indicated that "Mimi o Sumaseba" contains discipline values, including rules, habits, punishments, rewards, and consistency. This study reveals the content of discipline values focused on an anime film.